Online games as a space for identity construction: a perspective from the magic circle in League of Legends (Simbiótica. Revista Eletrônica, 2024)
This article investigates identity construction in online games, focusing on the perspective of the magic circle in League of Legends. The aim is to understand how players' identities are configured. The theoretical discussion includes problematizing the concepts of the magic circle in online games and identity construction in these environments. Through a qualitative methodological approach, the study provides an understanding of the effect of the magic circle. Within this space, players not only participate but also forge and inhabit their identities, consolidating League of Legends as a dynamic, multifaceted, and immersive environment where audiovisual elements, interactions, and narratives converge to create unique and personalized experiences. Through them, players reveal traits of themselves and incorporate new identity facets originating from these in-game constructions into their selves, suggesting an important role of these digital environments in the subject's identity constitution.
Keywords: online games; magic circle; identity; League of Legends